ANALISA PENGARUH PENGGUNAAN AIR PAYAU PADA CAMPURAN BETON NORMAL DENGAN VARIASI MERK SEMEN TERHADAP KUAT TEKAN - Albert; Suryanto (Politeknik Sampit, 2021)
This study focuses on observing how much damage to concrete in the mixing and maintenance process using brackish water with variations in the type of cement brand and its effect on the compressive strength of concrete K-175 (Normal Concrete) with curing 28 days and knowing the relationship between the modulus of elasticity and strain on the compressive strength of concrete. The results showed that the highest compressive strength of concrete at the design age of 28 days was 253.790 Kg/cm² or 20,447 MPa using brackish water and a mixture of Gresik cement materials followed by Tiga Roda cement of 20.313 MPa, Conc cement of 19,506 MPa and Holcim cement of 17,236 MPa. So that the relationship between compressive strength and modulus of elasticity and strain due to cement variations shows a value of R = 0.9999 or reaches a value of 1 so that it has a very significant effect.